SCHOOL CLIMATE INDICES AND ACADEMIC PERFORMANCE OF JUNIOR SECONDARY SCHOOL STUDENTS - Iheanyichukwu, Temidayo; BUKKI, Abolaji Olugbenga; FALADE , Enitan Omolara; EKEH , Agustina Ngozi; AIGBEKAEN, Alana Cynthia (African Journal of Behavioural and Scale Development Research, 2022)
Several efforts have been made towards improving the student's scholastic performance as this affects the quality of human resources in the country. This study assessed the influence of some school climate indices (teachers’ support, peer support and students’ autonomy) on the junior secondary students' academic performance in Ikorodu, Lagos State. Three hypotheses were developed; a descriptive research design was used to conduct the study. 300 children and 300 teachers were randomly selected as part of a sample of 600 responses. The instrument used was the school climate indices scale (SCIS), and the student academic report. Test-retest reliability yielded a correlation coefficient of 0.79, 0.75, 0.68, and 0.89. The data collected was analyzed using regression analysis at a 0.05 significance level. This study revealed that school climate indices significantly determine students’ academic performance. It was recommended among others that all institutions must reconsider the school climate indices and do the needful to develop the scholastic ratings of their students.